2007
DOI: 10.1083/jcb.200609178
|View full text |Cite
|
Sign up to set email alerts
|

Compartmentalization of androgen receptor protein–protein interactions in living cells

Abstract: Steroid receptors regulate gene expression in a ligand-dependent manner by binding specific DNA sequences. Ligand binding also changes the conformation of the ligand binding domain (LBD), allowing interaction with coregulators via LxxLL motifs. Androgen receptors (ARs) preferentially interact with coregulators containing LxxLL-related FxxLF motifs. The AR is regulated at an extra level by interaction of an FQNLF motif in the N-terminal domain with the C-terminal LBD (N/C interaction). Although it is generally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
116
1
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 143 publications
(126 citation statements)
references
References 38 publications
7
116
1
2
Order By: Relevance
“…It is believed that the immobile fraction of AR measured in FRAP assays corresponds to the chromatin-bound receptor during the transcription activation process, because of the overlap of AR locations with the sites of RNA synthesis (17). There is also a strong correlation between AR activity and the immobile fraction, as observed for AR WT and AR T878A stimulated with agonists and antagonists (43).…”
Section: Ligand-induced Intranuclear Behavior Of Mutant Receptorsmentioning
confidence: 53%
See 3 more Smart Citations
“…It is believed that the immobile fraction of AR measured in FRAP assays corresponds to the chromatin-bound receptor during the transcription activation process, because of the overlap of AR locations with the sites of RNA synthesis (17). There is also a strong correlation between AR activity and the immobile fraction, as observed for AR WT and AR T878A stimulated with agonists and antagonists (43).…”
Section: Ligand-induced Intranuclear Behavior Of Mutant Receptorsmentioning
confidence: 53%
“…Acceptor photobleaching fluorescence resonance energy transfer Acceptor photobleaching fluorescence resonance energy transfer (FRET) was performed using a Zeiss LSM510 confocal laser scanning microscope equipped with a Plan-Neofluar 40Â/1.3 NA oil objective (Carl Zeiss) at a lateral resolution of 100 nm (17). For excitation of CFP and YFP, an Argon laser at 358 and 514 nm was used.…”
Section: Double-hybrid Assaymentioning
confidence: 99%
See 2 more Smart Citations
“…In the presence of 1 nM R1881 both GFP-AR and GFP-AR F826L were translocated in a similar way to the nucleus and displayed a typical punctuate nuclear distribution pattern ( Figures 3C and 3D). This typical speckled pattern indicates an active transcription of endogenous genes (Farla et al, 2005;van Royen et al, 2007). It can be concluded that the F826L mutation did not influence the sub-cellular distribution of the AR mutant F826L.…”
Section: Sub-cellular Distribution Of Ar Mutant F826lmentioning
confidence: 92%